2018 Practice guidelines for the management of arterial hypertension of the European Society of Cardiology and the European Society of Hypertension. (2nd November 2018) - Williams, Bryan; Mancia, Giuseppe; Spiering, Wilko; Agabiti Rosei, Enrico; Azizi, Michel; Burnier, Michel; Clement, Denis; Coca, Antonio; De Simone, Giovanni; Dominiczak, Anna; Kahan, Thomas; Mahfoud, Felix; et al.
ABSTRACT: These practice guidelines on the management of arterial hypertension are a concise summary of the more extensive ones prepared by the Task Force jointly appointed by the European Society of Hypertension and the European Society of Cardiology. These guidelines have been prepared on the basis of the best available evidence on all issues deserving recommendations; their role must be educational and not prescriptive or coercive for the management of individual subjects who may differ widely in their personal, medical and cultural characteristics. The members of the Task Force have participated independently in the preparation of these guidelines, drawing on their academic and clinical experience and by objective examination and interpretation of all available literature. A disclosure of their potential conflict of interest is reported on the websites of the ESH and the ESC.